Preizkusna raziskava sinhronizacije dvovretenske stružnice - Kosmol, Jan (Strojniški vestnik, 2007)
In this paper we show the results of an experimental investigation of a VENUS 350 lathe, manufacture by CBKO in Pruszkow, Poland. This CNC lathe is equippedwith two spindles. We have measured the rotational speeds of both spindles, the synchronization error and the driven moments of the motors, mainand opposite. With this information it was possible to evaluate the process of synchronization.
Keywords: stružnice; sinhronizacija; vrtilna hitrost; servopogoni; Navar; navor